Kepuasan Kerja : Antecedent dan Konsekuensi (Studi Empiris pada Pengelola Destinasi Wisata Nepal Van Java-Magelang) - Rosiana Kamalinda; Diesyana Ajeng Pramesti (Universitas Muria Kudus, 2022)
ABSTRACTThis study aims to examine the effect of Organizational Citizenship Behavior and Job Insecurity on Good Governance Practices with Job Satisfaction as a Mediation Variable. The sample of this research is the managers of